Adenosine dihydroxysuccinate eutectic crystal as well as preparation method and application thereof

Through the formation of common crystals with dihydroxyl -hydroxyl acid, the water solution of adenosine is improved, the problem of low water -soluble in the existing adenosine common crystals is solved, and the better application effect in skin care products is achieved.

CN119350416AActive Publication Date: 2025-01-24SHENZHEN SHINESKY BIOLOGICAL TECH CO LTD

Patent Information

Application Number
CN202411897521.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-01-24
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

The existing adenosine co-crystals have low water solubility, limited use scenarios, and the beauty effect needs to be further improved.

Method used

By forming a eutectic with dihydroxysuccinic acid, the water solubility of adenosine is increased to 4%, and it shows better effects in antibacterial, antioxidant, anti-aging, hair care and anti-hair loss.

Benefits of technology

The high -water solubility of adenosine has enhanced its application potential in skin care products, and shows excellent results in multiple beauty.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350416A_ABST
    Figure CN119350416A_ABST
Patent Text Reader

Abstract

The invention provides an adenosine dihydroxysuccinate eutectic crystal and a preparation method and application thereof.In the adenosine dihydroxysuccinate eutectic crystal, the molar ratio of a dihydroxysuccinic acid molecule to an adenosine molecule is 1: (1-4), on the premise that the structure of adenosine is not changed, dihydroxysuccinic acid and adenosine are combined, the water solubility of adenosine is improved, and therefore the adenosine dihydroxysuccinate eutectic crystal is obtained. According to the preparation method, the adenosine which is difficult to dissolve in water is prepared into the water-soluble adenosine dihydroxysuccinate eutectic crystal, so that the water solubility of the adenosine dihydroxysuccinate eutectic crystal can reach 4%, the effects of the adenosine dihydroxysuccinate and the adenosine monomer are not damaged, and the adenosine dihydroxysuccinate and the adenosine monomer have a better synergistic effect; compared with a monomer and a simple mixture, the composition has better effects in the aspects of antibiosis, antioxidation, anti-aging, hair care, hair loss prevention and the like, and has a good application prospect in skin and hair care products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to eutectic technology and the field of daily chemical industry, and in particular to a dihydroxyadenosine eutectic and a preparation method and application thereof. Background Art

[0002] Adenosine is an active substance with nucleosides and purines as its basic structure. It is a nucleoside formed by adenine binding to D-ribose through a β-glycosidic bond. It is widely present in all types of cells and can be either free or combined nucleosides in nucleic acids. Adenosine, as a natural nucleotide, is an intermediate product of body metabolism and one of the important active ingredients in the body. It plays a key role in the energy metabolism process in cells by participating in the synthesis and degradation of ATP (adenosine triphosphate) and ADP (adenosine diphosphate). It is an important energy carrier in biochemical reactions. Adenosine can inhibit inflammatory reactions and the activation of immune cells, help maintain homeostasis in the body, and can also act on vascular smooth muscle to cause vasodilation, thereby affecting the relaxation and contraction of blood vessels and regulating blood flow. Due to its important physiological activity, adenosine has important application potential in skin care products as a nutritional adjuvant. However, adenosine has poor solubility and is slightly soluble in water, making it difficult to add a large amount to conventional skin care product formulas. It is also almost insoluble in ethanol and cannot be solubilized with alcohol, which limits its use scenarios.

[0003] Dihydroxysuccinic acid, also known as tartaric acid, has the chemical formula C4H6O6. It is a polybasic organic acid that occurs naturally in many fruits, especially grapes and lemons. Dihydroxysuccinic acid is a white crystalline powder or needle-shaped crystal with a typical sour taste. It is used in the food industry and the pharmaceutical field. In the food industry, tartaric acid is often used as an acidity regulator, antioxidant and stabilizer tartrate. It is also used as a cleaning agent and detergent. In the pharmaceutical field, dihydroxysuccinic acid and its salts can be used in the preparation of therapeutic drugs, such as antacids and injections.

[0004] In recent years, cocrystal formation has become a viable strategy to improve the stability and bioavailability of active pharmaceutical ingredients. By co-crystallizing the active ingredient with a coformer, a new solid state form with unique properties compared to the active ingredient is formed, thereby improving the drug formulation and improving its stability and bioavailability. However, cocrystal formation is unpredictable and is not always possible in fact. In addition, there is no way to predict the properties of a specific cocrystal before the compound is formed. Finding the right coformer and appropriate conditions to obtain a specific cocrystal requires researchers to spend more creative work.

[0005] Chinese patent CN117143164A "An adenosine co-crystal, its preparation method and application" discloses an adenosine co-crystal formed by adenosine and ectoine or nicotinamide in a molar ratio of 1:0.2~16.9, which has higher solubility than adenosine, but the water solubility of the obtained adenosine co-crystal is generally around 1.5%, the usage scenarios are still relatively limited, and the cosmetic effect still needs to be further improved.

[0006] Therefore, it is of great significance to provide a dihydroxyadenosine succinate co-crystal with high water solubility and excellent cosmetic effect, and a preparation method and application thereof. Summary of the invention

[0007] In view of the fact that the existing adenosine co-crystals have low water solubility, the usage scenarios are still relatively limited, and the cosmetic effect still needs to be further improved, the present invention provides a dihydroxysuccinate adenosine co-crystal and a preparation method and application thereof, which improve the water solubility of adenosine without changing the structure of adenosine itself, and prepare adenosine that is difficult to dissolve in water into a water-soluble dihydroxysuccinate adenosine co-crystal, so that the water solubility of the dihydroxysuccinate adenosine co-crystal can reach 4%. Not only does it not destroy the efficacy of dihydroxysuccinic acid and adenosine monomers, but the two also synergize to exert better effects. It has better efficacy than monomers and simple mixtures in antibacterial, antioxidant, anti-aging, hair care and anti-hair loss, etc., and has good application prospects in skin care and hair care products.

[0008] To achieve the above object, the technical solution adopted by the present invention is: A dihydroxysuccinate adenosine cocrystal, wherein the molar ratio of the dihydroxysuccinic acid molecule to the adenosine molecule is 1:(1-4).

[0009] Adenosine is a purine nucleoside, a compound formed by connecting the N-9 of adenine and the C-1 of D-ribose through a β-glycosidic bond. It is essentially an endogenous purine nucleotide, mainly formed by the dephosphorylation of adenosine triphosphate. It has always been used as a functional ingredient to dilate blood vessels and promote blood circulation. When the hair follicles become smaller or are in the resting phase, adenosine can send out cAMP energy signals, stimulate anti-hair loss factors, and reduce hair loss. Adenosine can not only stimulate hair growth, increase the production rate of FGF-7 factors and hair, but also directly act on dermal papilla cells to increase the growth rate of new and existing hair.

[0010] Organic cocrystals are crystalline single-phase materials composed of two or more components in a certain stoichiometric ratio. The components are connected by non-covalent bonds (such as hydrogen bonds, halogen bonds, π-π and charge transfer interactions, etc.). Cocrystal engineering provides an opportunity to achieve non-covalent synthesis of functional molecules. Its physical and chemical properties are determined by the intermolecular interactions and relative stacking structures between the donor and the acceptor. Cocrystal components self-assemble through hydrogen bonds or non-covalent bonds with saturation and direction (such as van der Waals forces of aromatics or benzene rings, π-π conjugation and halogen bonds), without destroying the existing covalent bonds. While retaining the effects of the active substance itself, it can also modify the physical and chemical properties of the active substance, such as improving stability, reducing irritation, improving solubility, and improving bioavailability.

[0011] Dihydroxysuccinic acid is a carboxylic acid found in many plants, such as grapes and tamarind, and is also one of the main organic acids in wine. Dihydroxysuccinic acid has the properties of dissolving keratin and astringency, which helps promote skin cell activation. When combined with adenosine to form a cocrystal of dihydroxysuccinic acid adenosine, it can greatly improve the solubility of adenosine and exert better efficacy.

[0012] Furthermore, the molar ratio of dihydroxysuccinic acid to adenosine in the dihydroxysuccinate adenosine cocrystal is 1:1; the cocrystal has an X-ray powder diffraction pattern represented by 2θ angle values, comprising the following 2θ angle values: 7.44°±0.2°, 10.94°±0.2°, 11.79°±0.2°, 13.70°±0.2°, 14.74°±0.2°, 15.28°±0.2°, 16.39°±0.2°, 18.84°±0.2°; in the infrared spectrum of the cocrystal, at 2500 cm -1 -3500 cm -1 There is a characteristic broad peak at 1706 cm -1 , 1606cm -1 , 1063 cm -1 There are characteristic peaks.

[0013] Furthermore, the molar ratio of dihydroxysuccinic acid to adenosine in the dihydroxysuccinate adenosine cocrystal is 1:4; the cocrystal has an X-ray powder diffraction pattern expressed in 2θ angle values, comprising the following 2θ angle values: 7.49°±0.2°, 10.79°±0.2°, 11.89°±0.2°, 13.68°±0.2°, 14.94°±0.2°, 15.47°±0.2°, 16.22°±0.2°, 18.87°±0.2°.

[0014] Furthermore, the water solubility of the eutectic is 4%.

[0015] Another object of the present invention is to provide a method for preparing two dihydroxyadenosine succinate co-crystals.

[0016] A method for preparing adenosine dihydroxysuccinate cocrystal according to any of the above items, comprising the following steps: S1. mixing dihydroxysuccinic acid and adenosine uniformly, and adding a solvent dropwise to obtain a dihydroxysuccinic acid-adenosine-solvent mixture; S2. The dihydroxysuccinic acid-adenosine-solvent mixture described in S1 is ball-milled at 25-35 Hz for 10-30 times, with a single grinding time of 30-60 s and an interval time of 30 s; during the interval time, ultrasound is started at a frequency of 25-45 KHz; after the ball milling is completed, the sample is taken out and dried to obtain the dihydroxysuccinic acid adenosine cocrystal.

[0017] The ball milling method can significantly reduce the reaction activation energy, refine the grains, greatly improve the powder activity and improve the uniformity of particle distribution. The preparation of eutectics by ball milling is simple and easy to control. It can induce the interaction between organic molecules through mechanical force and promote the formation of eutectics. It has the advantages of simple operation, high yield, strong structure regulation ability, high cost-effectiveness, environmental friendliness, rapid synthesis, structural diversity and great application potential.

[0018] Furthermore, the molar ratio of the dihydroxysuccinic acid to adenosine in S1 is 1:(1-4); the mass ratio of the mixture of dihydroxysuccinic acid and adenosine in S1 to the solvent is 1:(0.01-0.1).

[0019] Preferably, since the ball milling method can obtain a better mixing effect by adding very little solvent, and in order to ensure the product yield and grinding effect, the solid to solvent ratio should be controlled at 1g:(0.01~0.1)g.

[0020] Furthermore, the solvent in S1 is one or more of water, methanol, ethanol, ether, acetone, and isopropanol.

[0021] Furthermore, the ball milling frequency in S2 is 30 Hz, and the single grinding time is 30 s.

[0022] Preferably, the frequency is set to 30 Hz to improve the grinding efficiency, the single grinding time is set to 30-60 s, especially to 30 s, and the intermittent time is set to 30 s, which can effectively alleviate the phenomenon of grinding heat, and the number of grinding times is set to 10-30 times, so that the reactants can be fully ground and promote their full reaction.

[0023] Furthermore, the ultrasonic frequency in S2 is 40KHz and the time is 20s.

[0024] Preferably, ultrasound and ball milling are performed alternately so that the powder can be fully mixed. The ultrasonic frequency is selected to be 25-45KHz, especially 40KHz, which can achieve the best mixing effect on powdered materials. The ultrasonic time is set to 20s, and the interval of 10s with ball milling is conducive to cooling the material and preventing overheating.

[0025] A method for preparing adenosine dihydroxysuccinate cocrystal according to any of the above items, comprising the following steps: Step 1, mixing dihydroxysuccinic acid and adenosine, adding water, and stirring to form a suspension; Step 2: homogenize the suspension in step 1 at 50-200 bar high pressure for 2-5 times to obtain a mixed solution; Step 3, keep stirring the mixed solution in step 2, and react at 60-80°C for 4-8h; cool the solution after the reaction to -10-10°C, stir for crystallization, filter to obtain a solid, and vacuum dry to obtain the dihydroxysuccinic acid adenosine cocrystal.

[0026] The solvent method can quickly reduce the particle size of solid particles through high-pressure homogenization, promote uniform mixing of dihydroxysuccinic acid and adenosine, and at the same time, high pressure promotes the contact and reaction of dihydroxysuccinic acid and adenosine, thereby improving the reaction efficiency; maintaining stirring and increasing the temperature facilitates the uniform heating of dihydroxysuccinic acid and adenosine and sufficient reaction; cooling and crystallization can reduce impurities, thereby improving the purity of the product with less energy consumption, and stirring and crystallization can control crystal growth, and the obtained product has uniform particle size; since the reaction system is a water system, vacuum heating and drying in step S5 can improve drying efficiency, reduce drying time, and avoid bacterial colony growth.

[0027] Furthermore, in step 1, the molar ratio of dihydroxysuccinic acid to adenosine is 1:(1-4), and the mass ratio of the mixture of dihydroxysuccinic acid and adenosine to water is 1:(0.4-0.8).

[0028] Preferably, when the solid to water ratio is 1:(0.4-0.8), the product yield is higher.

[0029] Another object of the present invention is to provide an application of adenosine dihydroxysuccinate cocrystal.

[0030] An application of the above-mentioned adenosine dihydroxysuccinate cocrystal in daily chemical products.

[0031] Compared with the prior art, the present invention has the following advantages and beneficial effects: 1. The dihydroxyadenosine succinate co-crystal provided by the present invention improves the water solubility of adenosine without changing the structure of adenosine itself, and prepares adenosine, which is difficult to dissolve in water, into a water-soluble dihydroxyadenosine succinate co-crystal, so that the water solubility of the dihydroxyadenosine succinate co-crystal can be stably reached 4%.

[0032] 2. The adenosine dihydroxysuccinate cocrystal provided by the present invention does not destroy the efficacy of dihydroxysuccinic acid and adenosine monomers, and the two synergistically enhance each other to achieve better effects. It has better efficacy than monomers and simple mixtures in terms of antibacterial, antioxidant, anti-aging, hair care and anti-hair loss, and can be used in different skin care and hair care products.

[0033] 3. The preparation method of dihydroxysuccinate adenosine cocrystal provided by the present invention can obtain a better mixing effect by adding a small amount of solvent in the ball milling method. The ball milling and ultrasonic interleaving action have high grinding efficiency, small reaction loss, short reaction process and high product purity. The solvent method uses water as the solvent, which is green and environmentally friendly, has a simple reaction device, low cost, and is easy to industrialize and produce. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] The invention is further described using the accompanying drawings, but the embodiments in the accompanying drawings do not constitute any limitation to the invention. A person skilled in the art can obtain other drawings based on the following drawings without creative work.

[0035] Figure 1 This is the X-ray powder diffraction pattern of the dihydroxysuccinate adenosine cocrystal of Experimental Example 1 of the present invention.

[0036] Figure 2 This is the infrared spectrum of the dihydroxysuccinate adenosine cocrystal of Experimental Example 1 of the present invention.

[0037] Figure 3 This is a hydrogen nuclear magnetic resonance spectrum (1H-NMR) of the dihydroxyadenosine succinate cocrystal of Experimental Example 1 of the present invention.

[0038] Figure 4 This is a carbon nuclear magnetic resonance spectrum (13C-NMR) of the dihydroxyadenosine succinate cocrystal of Experimental Example 1 of the present invention.

[0039] Figure 5 This is the X-ray powder diffraction pattern of the dihydroxysuccinate adenosine cocrystal of Experimental Example 4 of the present invention.

[0040] Figure 6 This is a hydrogen nuclear magnetic resonance spectrum (1H-NMR) of the dihydroxyadenosine succinate cocrystal of Experimental Example 4 of the present invention.

[0041] Figure 7 It is the X-ray powder diffraction pattern of the material of Comparative Example 2 of the present invention.

[0042] Figure 8 It is a comparison diagram of the X-ray powder diffraction spectra of the dihydroxysuccinate adenosine cocrystal, dihydroxysuccinic acid and adenosine powder of the present invention.

[0043] Fig. 9Comparison diagram of infrared spectra of dihydroxysuccinate adenosine cocrystal, dihydroxysuccinic acid and adenosine of the present invention.

[0044] Fig.10 The diagram is a graph showing the morphology of hair follicles at different days in the in vitro hair follicle culture and hair growth test of the present invention.

[0045] Fig.11 It is a result diagram of the hair scale repair test of the present invention.

[0046] Fig.12 It is a statistical result diagram of the product recognition evaluation questionnaire of the present invention. DETAILED DESCRIPTION

[0047] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention is further described by the following examples. Obviously, the following examples are only part of the embodiments of the present invention, rather than all the embodiments; it should be understood that the embodiments of the present invention are only used to illustrate the technical effects of the present invention, rather than to limit the scope of protection of the present invention.

[0048] The raw materials in the examples can all be obtained commercially; unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0049] Example 1: A method for preparing adenosine dihydroxysuccinate cocrystal, comprising the following steps: Step 1: sterilize the reactor with 75% ethanol, completely dry the reactor, add 1.5009 kg of dihydroxysuccinic acid and 2.6724 kg of adenosine, add 2.0867 kg of water, and stir to form a suspension; Step 2: Pass the suspension described in step 1 through a high-pressure homogenizing valve at a pressure of 150 bar and cycle 4 times to obtain a mixed solution; Step 3: transfer the mixed solution described in step 2 to a stirred crystallization kettle, keep stirring, heat to 75°C, and react for 6 hours; cool the solution after the reaction to -5°C, stir and crystallize to obtain a solid; filter, and place the obtained solid in a vacuum drying oven for 16 hours at a drying temperature of 55°C to obtain the dihydroxysuccinic acid adenosine eutectic, wherein the molar ratio of dihydroxysuccinic acid to adenosine in the dihydroxysuccinic acid adenosine eutectic is 1:1.

[0050] The mass of adenosine dihydroxysuccinate cocrystal was weighed to be 3.7261 kg, and the calculated yield was 89.28%.

[0051] The obtained dihydroxysuccinate adenosine cocrystal was subjected to powder X-ray single crystal diffraction test, and the diffraction pattern is shown in Figure 1The results showed that the X-ray powder diffraction pattern (XRD) of the dihydroxysuccinate adenosine cocrystal had characteristic peaks at 2θ angles of approximately 7.44°±0.2°, 10.94°±0.2°, 11.79°±0.2°, 13.70°±0.2°, 14.74°±0.2°, 15.28°±0.2°, 16.39°±0.2°, and 18.84°±0.2°.

[0052] The obtained dihydroxyadenosine succinate cocrystal was subjected to infrared spectroscopy test. The infrared spectroscopy test results are as follows: Figure 2 The results show that the infrared spectrum of dihydroxysuccinate adenosine cocrystal is between 2500 and 3500 cm -1 There is a characteristic broad peak at 1706cm -1 , 1606 cm -1 , 1063cm -1 There are characteristic peaks.

[0053] The obtained dihydroxyadenosine cocrystal was characterized by 1H-NMR and 1H-NMR. 13 C-NMR) characterization, and the NMR spectra were as follows Figure 3 , Figure 4 shown. Figure 3 The nuclear magnetic resonance hydrogen spectrum shows that the nuclear magnetic resonance hydrogen spectrum ( 1 H-NMR) characterization, using D2O as the test solvent, from the H-NMR spectrum, two hydrogen atoms of dihydroxysuccinic acid and eight hydrogen atoms on adenosine can be clearly found; the rest are deuterated reagent peaks, and no obvious impurity peaks are found, indicating that in the dihydroxysuccinic acid adenosine cocrystal, dihydroxysuccinic acid and adenosine exist in a molar ratio of 1:1. Figure 4 The nuclear magnetic resonance carbon spectrum shows that the nuclear magnetic resonance carbon spectrum ( 13 C-NMR) characterization, using D2O as the test solvent, the test results showed that the dihydroxysuccinic acid and adenosine of the dihydroxysuccinic acid adenosine cocrystal existed in a molar ratio of 1:1.

[0054] Example 2: A method for preparing adenosine dihydroxysuccinate cocrystal, comprising the following steps: Step 1: sterilize the reactor with 75% ethanol, completely dry the reactor, add 1.5009 kg of dihydroxysuccinic acid and 2.6724 kg of adenosine, add 1.6693 kg of water, and stir to form a suspension; Step 2: Pass the suspension described in step 1 through a high-pressure homogenizing valve at a pressure of 100 bar for 4 cycles to obtain a mixed solution; Step 3: transfer the mixed solution described in step 2 to a stirred crystallization kettle, keep stirring, heat to 65°C, and react for 8 hours; cool the solution after the reaction to 0°C, stir and crystallize to obtain a solid; filter, and place the obtained solid in a vacuum drying oven for 24 hours at a drying temperature of 50°C to obtain the dihydroxysuccinic acid adenosine eutectic, wherein the molar ratio of dihydroxysuccinic acid to adenosine in the dihydroxysuccinic acid adenosine eutectic is 1:1.

[0055] The mass of the adenosine dihydroxysuccinate cocrystal was weighed to be 3.5826 kg, and the calculated yield was 85.85%.

[0056] Example 3: A method for preparing adenosine dihydroxysuccinate cocrystal, comprising the following steps: Step 1: sterilize the reactor with 75% ethanol, completely dry the reactor, add 1.5009 kg of dihydroxysuccinic acid and 2.6724 kg of adenosine, add 3.3386 kg of water, and stir to form a suspension; Step 2: Pass the suspension described in step 1 through a high-pressure homogenizing valve at a pressure of 120 bar for 3 cycles to obtain a mixed solution; Step 3: transfer the mixed solution described in step 2 to a stirred crystallization kettle, keep stirring, heat to 80°C, and react for 6 hours; cool the solution after the reaction to 4°C, stir and crystallize to obtain a solid; filter, and place the obtained solid in a vacuum drying oven for 18 hours at a drying temperature of 45°C to obtain the dihydroxysuccinic acid adenosine eutectic, wherein the molar ratio of dihydroxysuccinic acid to adenosine in the dihydroxysuccinic acid adenosine eutectic is 1:1.

[0057] The mass of the dihydroxysuccinate adenosine cocrystal was weighed to be 3.3697 kg, and the calculated yield was 80.74%.

[0058] Example 4: A method for preparing adenosine dihydroxysuccinate cocrystal, comprising the following steps: S1. 0.0750 g of dihydroxysuccinic acid and 0.5345 g of adenosine were mixed evenly, and 0.02 g of ethanol solution was added dropwise to obtain a hydroxysuccinic acid-adenosine-solvent mixture; S2. Place the dihydroxysuccinic acid-adenosine-solvent mixture in a ball mill, set the motor frequency to 30 Hz, the single grinding time to 30 s, the intermittent time to 30 s, and the number of grindings to 20 times; when the ball mill is in the intermittent time, start the ultrasonic device, the ultrasonic frequency is 40 KHz, and the time is set to 20 s; take out the sample after the ball milling, dry it, and obtain the dihydroxysuccinic acid adenosine cocrystal, the molar ratio of dihydroxysuccinic acid to adenosine in the dihydroxysuccinic acid adenosine cocrystal is 1:4.

[0059] The mass of the dihydroxysuccinate adenosine cocrystal was weighed to be 0.0.5492 g, and the calculated yield was 90.11%.

[0060] The obtained dihydroxysuccinate adenosine cocrystal was subjected to powder X-ray single crystal diffraction (XRD) test, and the diffraction pattern is shown in Figure 5 The results showed that the X-ray powder diffraction pattern of the dihydroxysuccinate adenosine cocrystal had characteristic peaks at 2θ angles of 7.49°±0.2°, 10.79°±0.2°, 11.89°±0.2°, 13.68°±0.2°, 14.94°±0.2°, 15.47°±0.2°, 16.22°±0.2°, and 18.87°±0.2°.

[0061] The obtained dihydroxysuccinate adenosine cocrystal was characterized by nuclear magnetic resonance hydrogen spectrum (1H-NMR). Figure 6 The results showed that D2O was selected as the test solvent through nuclear magnetic resonance hydrogen spectrum characterization. From the nuclear magnetic resonance hydrogen spectrum, 2 hydrogen atoms of dihydroxysuccinic acid and 32 hydrogen atoms on adenosine can be clearly found; the rest are deuterated reagent peaks, and no obvious impurity peaks are found. In the dihydroxysuccinic acid adenosine cocrystal, dihydroxysuccinic acid and adenosine exist in a molar ratio of 1:4.

[0062] Example 5: A method for preparing adenosine dihydroxysuccinate cocrystal, comprising the following steps: S1. 0.1501 g of dihydroxysuccinic acid and 0.2672 g of adenosine were mixed evenly, and 0.02 g of isopropanol solution was added dropwise to obtain a hydroxysuccinic acid-adenosine-solvent mixture; S2. Place the dihydroxysuccinic acid-adenosine-solvent mixture in a ball mill, set the motor frequency to 30 Hz, the single grinding time to 30 s, the intermittent time to 30 s, and the number of grindings to 25 times; when the ball mill is in the intermittent time, start the ultrasonic device, the ultrasonic frequency is 40 KHz, and the time is set to 20 s; take out the sample after the ball milling is completed, and dry it to obtain the dihydroxysuccinic acid adenosine cocrystal, and the molar ratio of dihydroxysuccinic acid to adenosine in the dihydroxysuccinic acid adenosine cocrystal is 1:1.

[0063] The mass of the dihydroxysuccinate adenosine cocrystal was weighed to be 0.3815 g, and the calculated yield was 91.42%.

[0064] Comparative Example 1: A method for preparing a substance, comprising the following steps: Step 1: sterilize the reactor with 75% ethanol, completely dry the reactor, add 1.5009 kg of dihydroxysuccinic acid and 2.6724 kg of adenosine, add 1.6693 kg of anhydrous ethanol, and stir to form a suspension; Step 2: Pass the suspension described in step 1 through a high-pressure homogenizing valve at a pressure of 120 bar for 3 cycles to obtain a mixed solution; Step 3: Transfer the mixed solution in step 2 to a stirred crystallization kettle, keep stirring, and heat to 65° C. If the solution cannot be dissolved, dihydroxysuccinic acid and adenosine do not react, and no product can be obtained.

[0065] Comparative Example 2: A method for preparing a substance, comprising the following steps: S1. 0.1501 g of dihydroxysuccinic acid and 0.2672 g of adenosine were mixed evenly, and 0.02 g of isopropanol solution was added dropwise to obtain a hydroxysuccinic acid-adenosine-solvent mixture; S2. Grind for 20 minutes; recover the sample to obtain the substance.

[0066] The weighed mass is 0.3279 g, and the calculated yield is 78.58%.

[0067] The obtained sample was subjected to powder X-ray single crystal diffraction test, and the diffraction pattern is shown in Figure 7 The results showed that the characteristic peaks in the X-ray powder diffraction pattern (XRD) of the sample could not correspond to the dihydroxyadenosine succinate cocrystal, and the product was not the dihydroxyadenosine succinate cocrystal. It was speculated that the conditions were not suitable, the reaction did not occur, or the reaction was uneven and insufficient.

[0068] The above embodiments and comparative examples were subjected to performance tests, and the experimental test methods were as follows: Powder X-ray single crystal diffraction test was performed on dihydroxysuccinic acid and adenosine monomers, and the obtained data were compared with the dihydroxysuccinic acid adenosine cocrystal prepared in Experimental Example 1 of the present invention. The comparison patterns of XRD diffraction of dihydroxysuccinic acid adenosine cocrystal, dihydroxysuccinic acid, and adenosine powder are as follows: Figure 8 shown.

[0069] Figure 8 The results show that the peaks in the powder X-ray single crystal diffraction spectrum of dihydroxysuccinic acid-adenosine cocrystal are not a simple superposition of the peaks of dihydroxysuccinic acid and adenosine monomers. This result indicates that new cocrystals are generated between dihydroxysuccinic acid and adenosine using the preparation method of the present invention.

[0070] The infrared spectra of dihydroxysuccinic acid and adenosine monomers were tested, and the obtained data were compared with the dihydroxysuccinic acid adenosine cocrystal. The infrared spectra comparison of dihydroxysuccinic acid adenosine cocrystal, dihydroxysuccinic acid, and adenosine are shown in the figure below. Fig. 9 shown.

[0071] Fig. 9 The results showed that the peaks in the infrared spectrum of dihydroxysuccinate-adenosine cocrystal are not simply the superposition of dihydroxysuccinic acid and adenosine monomer peaks, especially in the range of 2500-3500 cm-1 There is a characteristic broad peak, proving that hydrogen bonds are formed in the system. This result shows that dihydroxysuccinic acid and adenosine form a new cocrystal.

[0072] (1) Study on the water solubility of adenosine dihydroxysuccinate cocrystal The dihydroxyadenosine succinate cocrystals obtained in Experimental Examples 1 to 5 were dissolved in water to prepare a supersaturated solution under magnetic stirring. The sample was filtered and the content of the dihydroxyadenosine succinate cocrystal was tested by high performance liquid chromatography. The test results are shown in Table 1.

[0073] Table 1 Results of HPLC determination of content of adenosine dihydroxysuccinate cocrystal

[0074] The test results in Table 1 show that the water solubility of the adenosine dihydroxysuccinate cocrystals obtained in Experimental Examples 1 to 5 is all above 4%, which is much higher than the water solubility of adenosine, indicating that the water solubility of adenosine is greatly improved after adenosine and dihydroxysuccinic acid form a cocrystal.

[0075] (2) Study on the antibacterial ability of dihydroxysuccinate adenosine cocrystal against Propionibacterium acnes The experimental materials used in this example are: dihydroxysuccinic acid adenosine cocrystal obtained in Experimental Example 1, adenosine, and a physical mixture of dihydroxysuccinic acid adenosine prepared in a molar ratio of 1:1 with dihydroxysuccinic acid and adenosine. The antibacterial ability of the above samples against Propionibacterium acnes is tested. According to the suspension quantitative method, the sample to be tested is mixed with the test bacteria for a specified time, and the total number of colonies is determined and compared with the control group to calculate the antibacterial rate to evaluate its antibacterial effect. The results of the sample's effect on the test bacteria are shown in Table 2. For specific experimental steps, refer to QB / T 2738-2012 "Evaluation Method for Antibacterial and Antibacterial Effects of Daily Chemical Products".

[0076] Table 2 Results of the effects of samples on the test bacteria

[0077] The test results in Table 2 show that the dihydroxyadenosine succinate eutectic obtained in Example 1 has an antibacterial rate of 99.75% on Propionibacterium acnes after 5 minutes of action at a test concentration of 0.5%, and has a strong antibacterial effect on Propionibacterium acnes. The dihydroxyadenosine physical mixture has an antibacterial rate of 27.69% on Propionibacterium acnes after 5 minutes of action at a test concentration of 0.5%, and has no antibacterial effect on Propionibacterium acnes. Adenosine has an antibacterial rate of 43.08% on Propionibacterium acnes after 5 minutes of action at a test concentration of 0.32%, and has no antibacterial effect on Propionibacterium acnes. At equimolar test concentrations, the dihydroxyadenosine eutectic, adenosine, and the dihydroxyadenosine physical mixture have no antibacterial effect on the monomer and the physical mixture, but the dihydroxyadenosine eutectic has a strong antibacterial effect, showing its potential for application in acne removal products.

[0078] (3) Study on the free radical (DPPH) scavenging ability of dihydroxysuccinate adenosine cocrystal 1,1-Diphenyl-2-trinitrophenylhydrazine (DPPH) is a stable long-lived free radical. Its ethanol solution is dark purple and has strong absorption near 517nm. When there is a free radical scavenger, the light absorption of DPPH ethanol solution is weakened due to pairing with its single electron. The degree of fading of DPPH ethanol solution is linearly related to the number of electrons it accepts, which can be used to evaluate the ability of the test sample to scavenge free radicals, that is, the size of the antioxidant activity.

[0079] The detection method adopts T / SHRH 006-2018 "Cosmetics-Free Radical (DPPH) Scavenging Experimental Method". Set up sample tubes (T), sample backgrounds (T0), DPPH tubes (C) and solvent backgrounds (C0). Three parallel tubes are required for each sample tube (T) of each tested concentration of each sample. Add 1mL of sample solution of the same concentration to each sample tube (T) and sample background (T0). Add sample solvent to the sample background (T0) and solvent background (C0) to make up to 2mL and mix well. Add 1mL of DPPH ethanol solution to the sample tube (T) and DPPH tube (C), shake gently, and let stand at room temperature for 5min. Transfer the solution in each reaction tube into a 1cm cuvette and measure the absorbance at 517nm.

[0080]

[0081] The experimental materials used in this test example are: the adenosine dihydroxysuccinate eutectic obtained in Experimental Example 1, adenosine, dihydroxysuccinic acid, and a physical mixture of adenosine dihydroxysuccinate prepared in a molar ratio of 1:1 with adenosine dihydroxysuccinic acid. The results of the scavenging rates of adenosine dihydroxysuccinate eutectic, adenosine, dihydroxysuccinic acid, and a physical mixture of adenosine dihydroxysuccinate on DPPH free radicals are shown in Tables 3 to 6.

[0082] Table 3 Scavenging rate of adenosine dihydroxysuccinate cocrystal on DPPH free radicals

[0083] Table 4 Scavenging rate of adenosine on DPPH free radicals

[0084] Table 5 Scavenging rate of dihydroxysuccinic acid on DPPH free radicals

[0085] Table 6 Scavenging rate of physical mixture of adenosine and dihydroxysuccinic acid on DPPH free radicals

[0086] Statistical method in Tables 3 - 6: Analysis was carried out using the t - test method, with the test level α = 0.05; P≥0.05 indicates no statistical difference; 0.01 < P < 0.05 indicates significant difference; P < 0.01 indicates very significant difference; P < 0.001 indicates extremely significant difference. The statistical methods used in the following test examples are the same as those in this test example.

[0087] The results in Tables 3 - 6 show that due to solubility limitations, adenosine and the physical mixture of adenosine dihydroxysuccinate cannot increase the concentration and have almost no scavenging effect on DPPH free radicals within the experimental concentration range, and do not have antioxidant ability. For dihydroxysuccinic acid, as the concentration increases, the scavenging rate of DPPH free radicals no longer rises and remains at about 15%. However, the adenosine dihydroxysuccinate cocrystal improves solubility, has a higher concentration than adenosine and the physical mixture of adenosine dihydroxysuccinate, and the scavenging rate of DPPH free radicals shows a concentration - dependence. As the content increases, the scavenging rate increases, far higher than that of dihydroxysuccinic acid, and has the best antioxidant effect.

[0088] (4)Study on the scavenging ability test of adenosine dihydroxysuccinate cocrystal on free radicals (ABTS + ) In the presence of an oxidant, ABTS is oxidized to ABTS + free radicals, and the solution will turn green and have a strong absorption at a wavelength of 734 nm in the ultraviolet region. When an antioxidant is added to the system, the generation amount of ABTS + will decrease, the solution color will become lighter, gradually changing from dark green to light green, and the absorbance at 734 nm will become smaller. Based on this, the ABTS + free radical scavenging rate of this substance is determined.

[0089] Reference for detection method: Ma Qingling. Study on Ultrasonic-Assisted Extraction of Uyghur Medicine Celery Seed Protein Peptide Substances[J]. Anhui Agricultural Science, 2011, 39(18):3. Set appropriate mass concentration gradient according to sample characteristics, and prepare sample solutions for testing using PBS buffer as solvent. Set up sample tube (A S ), sample background (A b ), sample blank tube (A0), sample tubes for each tested concentration of each sample (A S ) need to set up 3 parallel tubes, and the sample blank tube (A0) also needs to set up 3 parallel tubes. S ) and sample background (A b ) were added with 0.2 mL of sample solution of the same concentration, and 0.2 mL of PBS buffer was added to the blank sample tube (A0). S ) and the sample blank tube (A0) were each added with 0.8 mL ABTS + Working solution, sample background (A b ) then add 0.8 mL PBS buffer. Incubate in dark for 6 min. Transfer the solution in each reaction tube into a 1 cm cuvette and measure the absorbance at 734 nm.

[0090]

[0091] The experimental materials used in this test example are: the adenosine dihydroxysuccinate eutectic obtained in Experimental Example 1, adenosine, dihydroxysuccinic acid, and a physical mixture of adenosine dihydroxysuccinate prepared in a molar ratio of 1:1. + The results of free radical scavenging rate are shown in Tables 7 to 10.

[0092] Table 7 Adenosine dihydroxysuccinate cocrystals to ABTS + Free radical scavenging rate

[0093] Table 8 Adenosine to ABTS + Free radical scavenging rate

[0094] Table 9 Dihydroxysuccinic acid to ABTS + Free radical scavenging rate

[0095] Table 10 Physical mixture of adenosine dihydroxysuccinate to ABTS + Free radical scavenging rate

[0096] Statistical methods in Tables 7 to 10: The t-test method was used for analysis, and the significance level α = 0.05; P ≥ 0.05 indicates no statistical difference; 0.01 < P < 0.05 indicates a significant difference; P < 0.01 indicates a very significant difference; P < 0.001 indicates an extremely significant difference.

[0097] The results in Tables 7 to 10 show that due to its solubility limitation, the physical mixture of adenosine and adenosine dihydroxysuccinate cannot increase the concentration and has almost no scavenging effect on ABTS + radicals within the experimental concentration range and does not have antioxidant ability. Dihydroxysuccinic acid has no scavenging effect on ABTS + radicals. However, the adenosine dihydroxysuccinate cocrystal improves solubility, has a higher concentration than the physical mixture of adenosine and adenosine dihydroxysuccinate, and has a high scavenging rate for ABTS + radicals, showing good antioxidant effects.

[0098] (5)Study on the inhibitory ability test of adenosine dihydroxysuccinate cocrystal on elastase activity Elastase (human leukocyte elas - tase, HLE) is a destructive enzyme present in the body that can hydrolyze certain connective tissue components such as elastin, proteoglycans, and certain types of collagen. Elastase can specifically hydrolyze substrates, and the absorbance value of p-nitroaniline (NA) decomposed at 382 nm is measured by spectrophotometry to calculate the enzyme activity and inhibition rate.

[0099] Reference for the detection method: Chen Liping, Yin Xiangli, Fang Yuchun, Hao Lijie, Zhao Feng. Establishment of a screening method for elastase inhibitors and observation of the inhibitory activity of natural products on it [J]. Journal of Yantai University (Natural Science and Engineering Edition), 2011, 24(03): 209 - 213. Set up sample tubes (A1), sample background tubes (A2), enzyme activity control groups (A3), and substrate blank groups (A4). Three parallel tubes are required for each test concentration of the sample in the sample tube (A1). Add 25 μL of the sample solution to the sample tube (A1) and the sample background tube (A2) respectively, and add the same volume of the sample solvent (PBS buffer or 10% DMSO) to replace the sample in the enzyme activity control group (A3) and the substrate blank group (A4). Add 225 μL of elastase solution to each tube in turn, mix well, and heat in a water bath at 37 °C for 5 min. Then add 250 μL of the substrate solution to the sample tube (A1) and the enzyme activity control group (A3) respectively, and add the same volume of 10% DMSO solution to the sample background tube (A2) and the substrate blank group (A4). Mix well and heat in a water bath at 37 °C for 30 min, and measure the absorbance value at a wavelength of 382 nm.

[0100]

[0101] The experimental materials used in this test example were: the adenosine dihydroxysuccinate cocrystal obtained in Experimental Example 1, adenosine, and the physical mixture of adenosine dihydroxysuccinate prepared by mixing adenosine and dihydroxysuccinic acid at a molar ratio of 1:1. The results of the inhibition rates of the adenosine dihydroxysuccinate cocrystal, adenosine, dihydroxysuccinic acid, and the physical mixture of adenosine dihydroxysuccinate on elastase are shown in Tables 11 to 13.

[0102] Table 11 Inhibition rate of adenosine dihydroxysuccinate cocrystal on elastase

[0103] Table 12 Inhibition rate of adenosine on elastase

[0104] Table 13 Inhibition rate of the physical mixture of adenosine dihydroxysuccinate on elastase

[0105] Statistical method in Tables 11 to 13: Analysis was performed using the t-test method, and the test level α = 0.05; P ≥ 0.05 indicates no statistical difference; 0.01 < P < 0.05 indicates a significant difference; P < 0.01 indicates a very significant difference; P < 0.001 indicates an extremely significant difference.

[0106] The results in Tables 11 to 13 show that due to the solubility limitation of adenosine and the physical mixture of adenosine dihydroxysuccinate, the concentration cannot be increased, and there is almost no inhibition of elastase within the experimental concentration range, so it does not have a firming effect. However, the adenosine dihydroxysuccinate cocrystal improves solubility, and the inhibition rate of elastase can reach more than 90% within the test range, showing a good firming and anti-aging effect.

[0107] (6) Test study on the inhibitory ability of adenosine dihydroxysuccinate cocrystal on 5α-reductase 5α-reductase is a membrane protease dependent on nicotinamide adenine dinucleotide phosphate (NADPH). It is an important androgen-metabolizing enzyme in the skin and can irreversibly convert testosterone (T) into dihydrotestosterone (DHT). DHT is the most active androgen and can induce the sebaceous glands to secrete excessive oil. By inhibiting the activity of 5α-reductase to reduce the level of DHT can effectively relieve the excessive secretion of oil by the sebaceous glands.

[0108] Detection method: Weigh the sample accurately, pre-treat the sample and set aside. Add reagents to the well plate for pre-reaction, incubate at 37°C for 30 minutes. After the pre-reaction is completed, add enzyme reagents and continue the reaction, incubate at 37°C for 30 minutes. Add colorimetric reagent to each well, develop color in an incubator at 37°C in the dark, add stop solution and terminate the reaction. Measure the absorbance of each well on the machine test, record the data, and calculate the inhibition rate.

[0109] The experimental material used in this test example is: the dihydroxyadenosine succinate cocrystal obtained in Experimental Example 1. The results of the inhibition rate of dihydroxyadenosine succinate cocrystal on 5α-reductase are shown in Table 14.

[0110] Table 14 Inhibition rate of dihydroxysuccinate adenosine cocrystal on 5α-reductase

[0111] The results in Table 14 show that the sample adenosine dihydroxysuccinate cocrystal has a good inhibitory effect on 5α-reductase at a test concentration of 1%, indicating that the sample has a good oil control effect. It can be seen that the adenosine dihydroxysuccinate cocrystal of the present invention has a high application potential in oil control, acne removal, and products for seborrheic alopecia.

[0112] (7) Study on the effect of dihydroxysuccinate adenosine cocrystal on the expression level of TGF-β2 gene in human keratinocytes Transforming growth factor β2 is a multifunctional protein that affects cell growth, differentiation, and apoptosis in the skin. Studies have shown that alopecia areata is related to autoimmune mechanisms, and the expression of TGF-β2 is closely related to the onset of alopecia areata. The anti-hair loss effect of a sample can be reflected by detecting the expression of the TGF-β2 gene.

[0113] Detection method reference: [1] Danielpour D, Dart LL, Flanders KC, etal.lmmunodetection and quantitation of the two forms of transforming growthfactor-beta (TGF-beta 1 and TGF-beta 2) secreted by cells in culture.[.Journal ofCellular Physiology, 2010, 138(1): 79-86. Zhang Ruzhi, Zhu Wenyuan, Xie Fang, et al. Effects of niacinamide on TGF-β1 secretion and CXCR2 expression in keratinocytes after ultraviolet irradiation[J]. Chinese Journal of Dermatology and Venereology, 2008, 22(3):3. Guangbin Wang. Study on the Effect of Oleanolic Acid on the Expression of VEGF and TGF-β1 in the Skin Lesions of Androgenetic Alopecia Mice and Its Therapeutic Effect [D]. Luzhou Medical College, 2014. Experimental steps: (1) Cell seeding: Inoculate the human keratinocyte suspension into a 24-well plate and incubate for 24 h.

[0114] Solution preparation: Prepare the working solution of the test substance.

[0115] Drug addition: Perform grouping and drug addition, and culture for 24 h.

[0116] Testing: Collect the RNA of each group and perform fluorescence quantitative PCR to detect the expression of the TGF-β2 gene.

[0117] The experimental materials used in this test example are: the adenosine dihydroxysuccinate co-crystal obtained in Experimental Example 1, and the adenosine dihydroxysuccinate physical mixture prepared by mixing adenosine dihydroxysuccinate and adenosine at a molar ratio of 1:1. The test results of the above samples for the TGF-β2 gene expression and the inter-group statistical results are shown in Tables 15 to 16.

[0118] Table 15 Test results of different samples for TGF-β2 gene expression

[0119] Table 16 Inter-group statistical results

[0120] Statistical method in Tables 15 to 16: Analysis was performed using the t-test method, and the test level α = 0.05; P ≥ 0.05 indicates no statistical difference; 0.01 < P < 0.05 indicates a significant difference; P < 0.01 indicates a very significant difference; P < 0.001 indicates an extremely significant difference. Compared with the NC group, 0.01 < P < 0.05 is expressed as , P < 0.01 is expressed as , P < 0.00l is expressed as .

[0121] The results in Tables 15 to 16 show that at the same concentration, the adenosine dihydroxysuccinate co-crystal has the ability to inhibit the secretion of TGF-β2 at concentrations of 0.001% and 0.0005%, and is superior to the adenosine dihydroxysuccinate physical mixture (P < 0.05). Therefore, at this concentration, the anti-hair loss effect of the adenosine dihydroxysuccinate co-crystal > the adenosine dihydroxysuccinate physical mixture.

[0122] (8) Study on the hair growth test of adenosine dihydroxysuccinate co-crystal on in vitro hair follicle culture Based on the in vitro hair follicle culture experiment, the effects of different samples on hair growth were compared; the growth cycle of mouse vibrissa hair is synchronized with their age, and the vibrissa hair follicles isolated in vitro can be maintained in culture for up to 23 days in vitro. The use of organ culture methods to evaluate hair follicle growth is considered to have a high correlation with the in vivo system because the degree of hair growth can be observed as the sum of the functions of each cell. The in vitro model was used to study the promotion of hair by the samples.

[0123] Reference for detection method: [1] Fan Weixin, Zhu Wenyuan, Lei Tiechi. Study on in vitro culture of mouse vibrissa hair follicles[J]. Chinese Journal of Dermatology, 1999(01):28-30. [2] lida M, lhara S, Matsuzaki T. Hair cycle-dependent changes ofalkaline phosphatase activity in themesenchyme and epithelium in mousevibrissal follices[J]. Development, growth&differentiationvol,2007(04):185-195. [3] Ohn, J., Kim, KH,&Kwon, O. Evaluating hair growth promoting effects of candidate substance :Areview of research methods[Jl. Journal ofdermatological science, 2019(03):144-149. [4] Kang JI,Kim SC, Kim MK, Boo Hj, Jeon YJ Koh Ys, Yoo ES, Kang SM,Kang HK. Effects ofDieckola component of Ecklonia cave, on the promotion ofhair growth[J]. International journal of molecularscience,2012(5):6407-6423. [5]Yamauchi, Koichi, andAkira Kurosaka, Inhibition of glycogensynthase kinase-3 enhances the experession of alkaline phosphatase andinsulin-like growth factor -1 in human primary dermaml papilla cellculture and maintains mouse hair bulbs in organ culture[J]. Archives ofdermatological research2019(02):357-365. Experimental steps: (1) Place the isolated hair follicles in a culture medium and incubate at 37°C, 5% CO2 for 14 days, with 1 mL of culture medium in each well.

[0124] Solution preparation: Prepare the working solution of the test substance.

[0125] Dosing: Dosing is done in groups, and the solution is changed every 3 days.

[0126] Image analysis: The length of the vibrissa follicles was photographed every 7 days, and the morphological observation and measurement of the vibrissa follicle length were performed.

[0127] Detection: After collecting the mouse vibrissa hair follicles on the 15th day of culture, each group of hair follicles was transferred to a cryopreservation tube, added with PBS, and kept in a -80 ℃ refrigerator for later use. After the specimen was thawed, it was kept at 2 ℃~8 ℃ and added with PBS. The hair follicles were manually ground and the cells were broken by repeated freezing and thawing. The supernatant was carefully collected by centrifugation, and the VEGF content in the specimen was detected by ELISA.

[0128] The experimental materials used in this test example are: the dihydroxysuccinate adenosine eutectic obtained in Experimental Example 1, and the dihydroxysuccinate adenosine physical mixture prepared with a molar ratio of 1:1 between dihydroxysuccinic acid and adenosine. The test results of hair follicle growth of different samples and the statistical results between groups are shown in Tables 17 and 18, the test results of growth rate of different samples and the statistical results between groups are shown in Tables 19 and 20, and the test results of VEGF content of different samples and the statistical results between groups are shown in Tables 21 and 22. The results of hair follicle morphology observation on different days under the same concentration (0.025 mg / mL) are shown in the figure below. Fig.10 shown.

[0129] Table 17 Hair follicle growth test results of different samples

[0130] Table 18 Statistical results between groups

[0131] Table 19 Detection Results of Growth Rates of Different Samples

[0132] Table 20 Statistical Results between Groups

[0133] Table 21 Detection Results of VEGF Contents of Different Samples

[0134] Table 22 Statistical Results between Groups

[0135] Statistical method in Tables 17 - 22: The t - test method was used for analysis, and the significance level α = 0.05; P≥0.05 indicates no statistical difference; 0.01 < P < 0.05 indicates significant difference; P < 0.01 indicates very significant difference; P < 0.001 indicates extremely significant difference. Compared with the NC group, 0.01 < P < 0.05 is expressed as , P < 0.01 is expressed as , P < 0.001 is expressed as .

[0136] Tables 17 - 22 and Fig.10 The results show that in the in vitro hair follicle culture hair growth test, at the same concentration (0.025 mg / mL), the growth length, growth rate, and VEGF content of the adenosine dihydroxysuccinate cocrystal group are all better than those of the adenosine dihydroxysuccinate physical mixture (P < 0.05). Therefore, at this concentration, the hair growth promoting effect of adenosine dihydroxysuccinate cocrystal > adenosine dihydroxysuccinate physical mixture.

[0137] (9) Experimental Study on the Combing Power, Tensile Strength, and Cuticle Repair of Human Hair Strands in Vitro The cuticles of normal hair are arranged from the hair root to the hair tip like fish scales from the fish head to the fish tail. When the hair is damaged, the tips of the cuticles will翘起 and detach from the hair. The greater the degree of翘起, the greater the opening and closing degree of the cuticles. In severe cases, the cuticles may fall off. When the cuticles are翘起 and in an open - closed state or have fallen off, the hair becomes thick and loses its luster. The factors affecting the combability of a single hair include the combing coefficient between hair fibers and between hair fibers and the comb, hair diameter, hair rigidity, the presence of static electricity, etc. Hair care products can make the hair easier to comb by changing factors such as the combing coefficient, oiliness, and adhesiveness of the hair.

[0138] Hair care test method: Baseline dry hair test: The hair to be tested is fully moistened with running constant temperature water, treated with cleaning solution, and placed in a constant temperature and humidity chamber (20~25℃, 40%~60%) for more than 4 hours. It is then taken out and fixed in the test position for a combing cycle test.

[0139] Sample dry hair test: The hair to be tested is fully moistened with running constant temperature clean water, and the sample is evenly applied on the surface of the hair at a rate of 0.2g per gram of hair. The application time is about 30s, and it is allowed to stand for about 3-5min. After rinsing, it is placed in a constant temperature and humidity chamber (20~25℃, 40%~60%) for more than 4 hours, and then taken out and fixed in the test position for combing cycle test.

[0140] Record the combing work values ​​of the hair bundle tested by CTX texture analyzer before and after using the sample and perform data processing.

[0141] Anti-hair breakage test method: (1) Test before using the sample: The hair strand to be tested is fully moistened with running constant temperature clean water, treated with cleaning solution, placed in a constant temperature and humidity chamber [(26±2)℃, (60±10)%RH] to dry naturally for 24 hours, and then a single-strand tensile test is performed, and the test data of each time is recorded.

[0142] (2) Test after using the sample: Rinse the hair bundle to be tested with running constant temperature clean water or do not rinse it according to the sample usage instructions. Apply 0.2g of sample per gram of hair bundle or the amount in accordance with the sample usage instructions evenly on the surface of the hair. After leaving it for a period of time, rinse it and use a soft and clean surface paper to wipe the moisture on the surface of the hair or do not rinse it. Put the isolated hair into a constant temperature and humidity chamber [(26±2)℃, (60±10)%RH] to dry it naturally for 24 hours, and then perform a single-strand tensile test, and record the test data for each time.

[0143]

[0144] Where: C0: combing work (tensile strength) of the baseline test; Cs: Combing work (tensile strength) of sample treatment test The dihydroxyadenosine succinate eutectic obtained in Experimental Example 1 was used as the active ingredient to prepare a dihydroxyadenosine succinate eutectic shampoo. This method uses an apparatus to measure the combability of the hair before and after the sample is used, and the degree of reduction in combability is used to measure the effectiveness of the sample in improving combability. The descriptive statistical results of the combing work and the change rate of tensile strength before and after the sample is used are shown in Tables 23 and 24. The results of the hair scale repair test are shown in Figure 23. Fig.11 shown.

[0145] Table 23 Descriptive statistics of combing power change rate before and after using samples

[0146] Table 24 Descriptive statistics of the change rate of tensile strength before and after using the samples

[0147] Table 23~Table 24 and Fig.11 The results show that compared with before use, the combing work of the hair bundle is reduced, the tensile strength is increased, the hair is softer and stronger, the opening and closing of the hair scales is reduced, and the opening and closing of the hair scales is significantly improved.

[0148] (10) Evaluation and research on adverse reactions of cosmetic skin irritation The dihydroxysuccinate adenosine eutectic obtained in Experimental Example 1 was used as the active ingredient to prepare dihydroxysuccinate adenosine eutectic shampoo. Qualified patch test equipment was selected, and 0.020 g to 0.025 g of the test substance was placed in the patch test equipment by the closed patch test method, and the test substance was applied to the curved side of the forearm of the subject with a hypoallergenic tape. The test substance was removed after 24 hours, and the skin reaction was observed at 0.5, 24, and 48 hours after removal, and the results were recorded according to the skin reaction grading standard in the "Safety Technical Specifications for Cosmetics" (2015 edition). The results of the closed patch test on human skin are shown in Table 25.

[0149] Table 25 Summary of human skin patch test results

[0150] The results of the human skin occlusive patch test of dihydroxysuccinate adenosine eutectic shampoo showed that no adverse skin reactions occurred in 30 people.

[0151] (11) Experimental research on consumer product recognition evaluation The dihydroxysuccinate adenosine eutectic obtained in Experimental Example 1 was used as the active ingredient to prepare dihydroxysuccinate adenosine eutectic shampoo. After using the test product for 14 days and 28 days, the subjects evaluated the degree of recognition of the product-related indicators. The higher the percentage, the more people recognized the indicator. The statistical results of the product recognition evaluation questionnaire are as follows: Fig.12 shown.

[0152] Fig.12 The results showed that after using the test product for 14 days and 28 days, the subjects had high approval in terms of skin feel, oil control and anti-hair loss, and their overall evaluation was that they were satisfied with the product as a whole, with significant differences.

[0153] In summary, the present invention improves the water solubility of adenosine without changing the structure of adenosine itself, and prepares adenosine, which is difficult to dissolve in water, into a water-soluble adenosine dihydroxysuccinate cocrystal, so that the water solubility of the adenosine dihydroxysuccinate cocrystal can reach 4%. Not only does it not destroy the efficacy of dihydroxysuccinic acid and adenosine monomers, but the two synergistically enhance each other to exert a better effect. It has better efficacy than monomers and simple mixing in many aspects such as antibacterial, antioxidant, anti-aging, hair care and anti-hair loss, and has good application prospects in skin care and hair care products.

[0154] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A dihydroxysuccinate adenosine cocrystal, characterized in that: The molar ratio of the dihydroxysuccinic acid molecule to the adenosine molecule is 1:(1-4).

2. A dihydroxyadenosine succinate cocrystal according to claim 1, characterized in that: The molar ratio of dihydroxysuccinic acid to adenosine in the dihydroxysuccinic acid adenosine cocrystal is 1:1; the cocrystal has an X-ray powder diffraction pattern represented by 2θ angle values, comprising the following 2θ angle values: 7.44°±0.2°, 10.94°±0.2°, 11.79°±0.2°, 13.70°±0.2°, 14.74°±0.2°, 15.28°±0.2°, 16.39°±0.2°, 18.84°±0.2°; in the infrared spectrum of the cocrystal, at 2500 cm -1 -3500 cm -1 There is a characteristic broad peak at 1706 cm -1 , 1606 cm -1 , 1063 cm -1 There are characteristic peaks.

3. A dihydroxyadenosine succinate cocrystal according to claim 1, characterized in that: The molar ratio of dihydroxysuccinic acid to adenosine in the dihydroxysuccinate adenosine cocrystal is 1:4; the cocrystal has an X-ray powder diffraction pattern expressed in 2θ angle values, comprising the following 2θ angle values: 7.49°±0.2°, 10.79°±0.2°, 11.89°±0.2°, 13.68°±0.2°, 14.94°±0.2°, 15.47°±0.2°, 16.22°±0.2°, 18.87°±0.2°.

4. A dihydroxyadenosine succinate cocrystal according to claim 1, characterized in that: The water solubility of the co-crystal is 4%.

5. A method for preparing adenosine dihydroxysuccinate cocrystal according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1. mixing dihydroxysuccinic acid and adenosine uniformly, and adding a solvent dropwise to obtain a dihydroxysuccinic acid-adenosine-solvent mixture; S2. The dihydroxysuccinic acid-adenosine-solvent mixture described in S1 is ball-milled at 25-35 Hz for 10-30 times, with a single grinding time of 30-60 s and an interval time of 30 s; during the interval time, ultrasound is started at a frequency of 25-45 KHz; after the ball milling is completed, the sample is taken out and dried to obtain the dihydroxysuccinic acid adenosine cocrystal.

6. A method for preparing adenosine dihydroxysuccinate cocrystal according to claim 5, characterized in that: The molar ratio of dihydroxysuccinic acid to adenosine in S1 is 1:(1-4); the mass ratio of the mixture of dihydroxysuccinic acid and adenosine in S1 to the solvent is 1:(0.01-0.1).

7. A method for preparing adenosine dihydroxysuccinate cocrystal according to claim 5, characterized in that: S1 The solvent is one or more of water, methanol, ethanol, ether, acetone, and isopropanol.

8. A method for preparing adenosine dihydroxysuccinate cocrystal according to any one of claims 1 to 4, characterized in that: The following steps are involved: Step 1, mixing dihydroxysuccinic acid and adenosine, adding water, and stirring to form a suspension; Step 2: homogenize the suspension in step 1 at 50-200 bar high pressure for 2-5 times to obtain a mixed solution; Step 3, keep stirring the mixed solution in step 2, and react at 60-80°C for 4-8h; cool the solution after the reaction to -10-10°C, stir for crystallization, filter to obtain a solid, and vacuum dry to obtain the dihydroxysuccinic acid adenosine cocrystal.

9. A method for preparing adenosine dihydroxysuccinate cocrystal according to claim 8, characterized in that: In step 1, the molar ratio of dihydroxysuccinic acid to adenosine is 1:(1-4), and the mass ratio of the mixture of dihydroxysuccinic acid and adenosine to water is 1:(0.4-0.8).

10. Use of the dihydroxyadenosine succinate cocrystal according to any one of claims 1 to 4 in daily chemical products.

Citation Information

Patent Citations

  • Adenosine eutectic and preparation method and application thereof

    CN117143164A

Cited By

  • Menthyl lactate and succinic acid eutectic cool-feeling acne removing agent and preparation method thereof

    CN121242975A

  • Adenosine supramolecular composition as well as preparation method and application thereof

    CN121891254A

  • An adenosyl-based supramolecular composition, and a method of preparing and using the same

    CN121891254B